OPTIMALISASI REDISTRIBUSI TANAH DALAM RANGKA PEMBAHARUAN AGRARIA (Study Program Redistribusi Tanah Obyek Landreform di Kabupaten Mempawah)â€ - TITIK KURNIA WATI, S.ST A.21212066, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis addresses the issue of purchase covert (undercover buy) a disclosure strategy narcotics (juridical-empirical studies in Pontianak) .This method used in this study is a qualitative research method using Normative-sociological approach. Covert purchase as regulated Act No. 22 of 1997 which has been changed to Law No. 35 of 2009 is the addition of investigator powers in efforts to combat drug trafficking. This is because the narcotic crime is organized crime, secret, as well as in the implementation modus operandi and quite sophisticated technology making it difficult to collect the evidence. In contrast to other offenses of purchasing shrouded in narcotic crime is not against the Human Rights when implemented in accordance with applicable regulations. This is because the narcotic crime is organized crime, secret, as well as in the implementation modus operandi and quite sophisticated technology making it difficult to collect the evidence. In contrast to other offenses of purchasing shrouded in narcotic crime is not against the Human Rights when implemented in accordance with applicable regulations. However, it would be different if it is not carried out in accordance with applicable regulations. This is because that in the implementation of covert purchases can not be separated and community participation, so that people who participate must be protected rights. To reduce errors and execution of the covert purchase it is necessary to be known and understood clearly by the investigator on the implementation of the purchase itself disguised as stipulated in Law No. 35 of 2009. The recommendation of this study is the need to be undertaken a revision of Law No. 35 Year 2009 on Narcotics itself in order to clarify what is the purchase of a veiled and how the actual implementation and the need to educate more people programmatically, for the use of informants to impersonate let conducted training Special to the investigator who was assigned to make the purchase is shrouded in a narcotics detective. and provide security to the people that specifies the information to the officer.Keywords: disclosure strategy, narcotics, Purchase veiled.ABSTRAKTesis ini membahas masalah pembelian terselubung (undercover buy) sebagai strategi pengungkapan kejahatan narkotika (studi yuridis-empiris di Kota Pontianak).Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan menggunakan pendekatan Normative-Sosiologis. Pembelian Terselubung sebagaimana diatur Undang-Undang No 22 Tahun 1997 yang telah diganti menjadi Undang-Undang No 35 Tahun 2009 merupakan penambahan kewenangan penyidik dalam upaya pemberantasan pengedaran narkotika. Hal inimengingat tindak pidana narkotika merupakan kejahatan yang terorganisasi, rahasia, serta dalam pelaksanaannya menggunakan modus operandi dan teknologi yang tergolong canggih sehingga sulit dalam mengumpulkan barang buktinya. Berbeda dengan tindak pidana lainnya pelaksanaan pembelian terselubung dalam tindak pidana narkotika tidaklah bertentangan dengan Hak Asasi Manusia bila dilaksanakan sesuai dengan peraturan yang berlaku. Akan tetapi, akan menjadi berbeda bila tidak dilaksanakan sesuai dengan peraturan yang berlaku. Hal ini dikarenakan bahwa dalam pelaksanaan pembelian terselubung tidak terlepas dan peran serta masyarakat, sehingga masyarakat yang ikut serta harus dilindungi hak-haknya. Untuk mengurangi kesalahan dan pelaksanaan pembelian terselubung tersebut maka perlu diketahui dan dipahami secara jelas oleh penyidik tentang pelaksanaan pembelian terselubung itu sendiri sebagaimana diatur dalam Undang-Undang No 35 Tahun 2009. Adapun rekomendasi dari penelitian ini adalah perlu kiranya dilakukan revisi terhadap Undang-Undang No 35 Tahun 2009 tentang Narkotika itu sendiri guna memperjelas apa itu pembelian terselubung dan bagaimana sebenarnya pelaksanaannya dan perlu dilakukan penyuluhan kepada masyarakat secara terprogram, untuk penggunaan informan untuk menyamar hendaklah dilakukan pelatihan secara khusus kepada penyidik yang memang bertugas untuk melakukan pembelian terselubung dalam suatu reserse narkotika. dan memberikan jaminan keamanan kepada masyarakat yang memerikan informasi kepada petugas.Kata Kunci: strategi pengungkapan, kejahatan narkotika, Pembelian terselubung.